A Comparative study of DAB and Arbitration as methods of resolving Construction Disputes - AL KHAWAJA, DANA JAMAL (2023)
This dissertation’s purpose is to briefly introduce reasons for construction field disputes and to discuss the various DR methods applicable to resolve them, and their advantages and disadvantages. It then proceeds to elaborate on two of these methods, namely arbitration and dispute adjudication boards and take a closer look at two important factors considered when a person decides to approach DR, which are time and cost for resolving disputes through them. The doctrinal nature of this study allows comparison between the two methods using information collected by credited researchers. It is intended to highlight the overlooked benefits of DAB, and encourage its application in the UAE, since it is supported by FIDIC only and not by statute. It is concluded that while the cost of international arbitration may be 15% of a project’s value and may take years to resolve, DAB takes less time. Although time limits increase efficiency relative to arbitration, the ICC rules set time limits for the tribunal’s formation and for submission of rejoinders, but not for the issuance of an award. DIAC rules however set a three-month limit that can be extended to five, from the date of transfer of the case from DIAC to the tribunal .